Improving salt diffusion by ultrasound application during wet salting of pork meat: A mathematical modeling approach - Sanches, Marcio Augusto Ribeiro [UNESP]; Lapinskas, Nicholas Matheus [UNESP]; Barretto, Tiago Luis [UNESP]; da Silva-Barretto, Andrea Carla [UNESP]; Telis-Romero, Javier [UNESP] (Wiley, 2022)
The objectives of this research were to evaluate the influence of ultrasound (US; power of 600 W; frequency of 20 kHz), and salt concentration (SC) in brine (50 and 100 g of salt·L−1 of water) on salt gain (SG) in salted pork meat and to investigate the applicability of mathematical models to simulate SG. Four treatments were tested: T50SB, static brine with 50 g of salt·L−1 of water; T100SB, static brine with 100 g of salt·L−1 of water; T50US, US-assisted brine with 50 g of salt·L−1 of water; T100US, US-assisted brine with 100 g of salt·L−1 of water. After wet salting, the NaCl content was determined by the Mohr method. Five mathematical models (Azuara; Z and L; Simplified Fick Equation; Weibull; Diffusive) were tested to describe SG. US-assisted brine and increasing SC in the brine increased (p <.05) the NaCl content in the salted meat. The salt diffusion coefficients also increased (p <.05) as a result of the increase in the SC in the brine and by the application of US (TM). All models tested showed predictability of experimental data and confirmed that US accelerated the SG during wet salting. The Azuara model presented the highest coefficients of determination (R2) and was chosen to predict the experimental data due to its best fit and because it has a simple mathematical solution, also enabling the prediction of equilibrium conditions. Therefore, US-assisted brine is a technology that can shorten the salting time and improve the salt diffusion in pork meat and the Azuara model can be used to simulate wet salting processes. Practical Applications: Ultrasound is an emerging technology that has shown promising results in the processing of meat and meat products. This study showed that ultrasound-assisted brine of pork meat improves SG, increasing the salt diffusion coefficient in salted meat. Therefore, ultrasound-assisted brine has the potential to shorten salting time in the industrial processing of pork meat. The Azuara model successfully described the kinetic parameters of the process and can be used to simulate the static and ultrasound-assisted brine process.
Keywords: diffusion coefficient; mathematical models; NaCl; process simulation; salt concentration; salt gain